PROPOSED MARKETING STRATEGY TO IMPROVE PRODUCT VALUE OF ERIGO USING PERCEPTION CHANGE STRATEGIES (The Indonesian Journal of Business Administration, 2019)
Creative economy’s sector is one of the most growth sector in Indonesia. Based on data from Badan Ekonomi Kreatif (Bekraf), creative economy’s sector in 2016 contributed 7,38% to the total of Indonesia Product Domestic Bruto (PDB). One of the most contributed sector is fashion’s sector that contributed as 18,15%. The high contribution of this sector showed an increasing demand of fashion industry products, and also creates high competitive condition. In 2016, the total number of local fashion brand is 1.230.988. High competition on fashion industry in Indonesia also caused by many foreign fashion companies enter to this industry.One of local fahion brand that compete in fashion industry in Indoneia is Erigo. Erigo is a small fashion company that offers fashion products with low price, so in business activity Erigo must minimizing their cost. The increasing of raw material price caused problem for Erigo because its increasing their production cost. As a fashion company that offers many purchase deal or discount as their marketing program, increasing their price will be irrelevant. Erigo need to formulate new marketing stategy to keep competing in fashion industry in Indonesia.To formulate new marketing strategy Erigo need to understand the behavior of their consumers. This research using consumer buying process to analyze the consumers behavior. Furthermore this research using product attribute’s analysis to understand product attributes that significantly affecting consumer purchase decision.The result of both analysis generate three new marketing strategies for Erigo to improve their product value. The strategies are changing the consumer’s basic motivational function, and associating the product with an admired group or event strategy.Keywords: Consumer Behavior, Consumer Buying Process, Analysis Product Attribute, Marketing Strategy.